Sosialisasi Dampak Kekerasan Intelektual (Calistung) Pada Kesehatan Mental Anak Usia Dini di RA Nursa'dani Medan - Azhima, Idzni; Khatijah, Titiek; Nafiah Harahap, Wirdatun (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Early childhood who have good academic abilities such as reading, writing, and arithmetic are the desire of all parents and are used as an indicator of success in educating children. However, in reality, children's success in learning to read, write, and count cannot be separated from the coercion of parents who want them to be able to read, write, and count after graduating from kindergarten. This treatment is a form of violence that parents unknowingly commit against their children, namely intellectual violence which also causes problems with children's mental health or is commonly called mental hectic. Mental hectic is a condition in which a person experiences a mental disorder characterized by an imbalance in emotions, actions, and thought patterns. Mental hectic can cause a person to experience confusion that leads to stress and depression. This research is a community service. The purpose of this service is to provide an understanding to parents and teachers about the impact of intellectual violence (calistung) on ​​the mental health of early childhood. The results of this community service show that parents and teachers understand that learning to read, write, and count (calistung) if taught to early childhood with abstract and unpleasant methods for children will have an impact on causing mental hectic or mental chaos and is included in the form of intellectual violence. On the other hand, if learning to read, write, and count (calistung) is carried out proportionally or in accordance with the development of the child's age and with a concrete concept, then learning to read, write, and count (calistung) can be a means of reducing the occurrence of mental hectic in early childhood.